2012
DOI: 10.1259/bjr/94315429
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the cervical spine with neck extension: is it useful?

Abstract: Objectives: Standard MRI of the cervical spine is performed in a different anatomical position to that utilised for traditional contrast myelography. Those well practised in myelography are familiar with the considerable changes in configuration of the bony and soft tissues of the cervical spine that may occur with changes in the degree of neck flexion and extension. We set out to compare the findings in a select group of patients with myeloradiculopathy who had undergone myelography and MRI in both standard a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 26 publications
3
34
0
3
Order By: Relevance
“…A second limitation was the single posture used for C-spine MRI, as the C-spine posture affects the dimensions of the neural foramen [10]. Bartlett et al [11] reported that cervical neural foramina are more likely to appear abnormal if the spine is extended and the foramina become narrowed. They suggested that MRI with neck extension might improve diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation was the single posture used for C-spine MRI, as the C-spine posture affects the dimensions of the neural foramen [10]. Bartlett et al [11] reported that cervical neural foramina are more likely to appear abnormal if the spine is extended and the foramina become narrowed. They suggested that MRI with neck extension might improve diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, the angle was measured as the difference in vertebrae angles at C2 and C7. 9,10 The angle between these 2 vertebrae is calculated by drawing a line parallel to the posterior edge of the vertebral body, which runs parallel to the spinal cord, and calculating the angle between those 2 lines. The far right artist's illustration depicts segmental rootlets and the formation of a spinal nerve root that emerges from the intervertebral foramen.…”
Section: Does Patient Positioning Within the Mr Imaging Environment Ementioning
confidence: 99%
“…Including these views increases the detection or exclusion of true instability [2, 6, 14-16]. In this study, we selected what we felt to be definable indicators of neuraxis injury using parameters on dynamic MRI.…”
Section: Discussionmentioning
confidence: 99%